Microfinance and forest-based small-scale enterprises (Rome, 2005)
Communities around the world rely on forests for their livelihoods, and the sustainable development of small-scale, often family-run enterprises is increasingly recognised as a key to poverty reduction. This publication examines the needs of such small-scale enterprises for access to microfinance services, given the seasonal and often unpredictable nature of forest-based activities. It looks at different types of financial institutions (such as banks, non-governmental organisations, co-operatives and credit unions) as well as group lending, leasing, insurance and cash transfers. The strengths and weaknesses of different approaches are considered through four case studies which draw on experiences in Nepal, Guatemala, the Sudan and Peru.
Keywords: Microfinance,Forests and forestry,Forest products industry; Economic aspects,Economic aspects